HUBUNGAN KEPUASAN KOMUNIKASI ORGANISASI DENGAN MOTIVASI KERJA PEGAWAI DI KANTOR SETWAN DPRD KOTA TASIKMALAYA - Andi Andi (LPPM STIA Banten, 2018)
In this research, what is tested is the relationship between organizational communication satisfaction with the work motivation of employees at the Regional People's Representative Council Secretariat Office Tasikmalaya City with reference to the Pearson Product Moment correlation coefficient as well t effect test and coefficient of determination to find out whether there is an effect or not between these two variables and in order to stabilize the results of this research. The data collection technique uses questionnaires and interview results to add narrative description of the questionnaire results. The average relationship between organizational communication satisfaction and employee work motivation at the City Regional People's Representative Council Secretariat Office Tasikmalaya is STRONG with a value of 0.731. This indicates work motivation closely related to and determined by organizational communication satisfaction.